The Effectiveness of the Papaya Mengkal and Green Grass Jelly Against the Decrease in the Blood Pressure of the Client's Mild Hypertension - Indriati Indriati; Rr Sri Endang Puji Astuti; Tuti Anggarawati; Yuni Astuti (Green Publisher Indonesia, 2022)
Hypertension is condition medical moment pressure blood in arteries increase exceed normal limit. Various study has conducted for see effectiveness plant in lower pressure blood high, such as papaya mengkal and green grass jelly. In one study said that there was a decrease in blood pressure in hypertensive clients after giving papaya juice. While green grass jelly is rich in flavonoid and alkaloid active substances. The content of flavonoid active substances can act as anti-hepatotoxic, anti-HIV1, anti-tumor, anti-inflammatory and can provide a vasodilating effect on blood vessels that helps protect heart function. Flavonoids can reduce arterial stiffness and can be an alternative treatment to reduce the risk of heart disease.